Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas IV Mata Pelajaran Pendidikan Agama Islam di UPTD SDN 02 Sungai Rimbang - Delfiyanti Delfiyanti; Syawaluddin Syawaluddin; Deslita Deslita; Dila Yanti Safitri; Yeni Susila; Hidayati Hidayati (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve the learning outcomes of fourth grade students in Islamic Religious Education (PAI) subjects at UPTD SDN 02 Sungai Rimbang through the application of the Problem Based Learning (PBL) learning model. The background of this research is the low student learning outcomes that require a more innovative and effective learning approach. The research method used is Classroom Action Research (PTK) with a cycle model consisting of planning, implementation, observation, and reflection. The subjects of this study were fourth grade students with a total of 10 students. The results showed that the application of the PBL learning model can significantly improve student learning outcomes in PAI subjects. The improvement can be seen from the increase in students' average scores from cycle I to cycle II, as well as students' positive responses to more interactive and challenging learning. Based on these findings, the application of PBL is recommended as one of the effective learning models to improve student learning outcomes in PAI subjects.